Transcription Factor T-Bet in Atlantic Salmon: Characterization and Gene Expression in Mucosal Tissues during Aeromonas Salmonicida Infection - Kumari, Jaya; Zhang, Zuobing; Swain, Trilochan; Chi, Heng; Niu, Cuijuan; Bøgwald, Jarl; Dalmo, Roy Ambli (Frontiers in Immunology, 2015)
The T-box transcription factor T-bet is expressed in a number of hematopoietic cell types in mammals and plays an essential role in the lineage determination of Th1 T-helper cells and is considered as an essential feature for both innate and adaptive immune responses in higher vertebrates. In the present study, we have identified and characterized the full-length Atlantic salmon T-bet cDNA (3502 bp). The putative primary structure of the polypeptide deduced from the cDNA sequence contained 612 aa, which possessed a T-box DNA binding domain. Phylogenetic study and gene synteny revealed it is a homologue to mammalian T-bet. Quantitative PCR analysis of different tissues in healthy fish showed that salmon T-bet gene was highly expressed in spleen, followed by head kidney, and was expressed in intestine, skin, and liver at lower levels. Moreover, the time dependent expression profile of T-bet, interferon gamma (IFNγ), interleukin-22 (IL-22), and NKEF (Natural killer enhancement factor) in mucosal tissues during waterborne infection with live Aeromonas salmonicida, indicated the involvement of T-bet in mucosal immune response in Atlantic salmon.